Is mmWave Ready for Cellular Deployment? - Siming Zhang; Guizhen Wang; Chih-Lin I (IEEE Access, 2017)
The wireless capacity crunch will undoubtedly continue as new innovative applications emerge, for instance, augmented reality and massive machine type communications. mmWave promises to deliver gigabits of bandwidth and unprecedented wireless capacity and has created quite the social buzz in both industry and academia. However, mmWave does come with its challenges. Some most prominent issues include high propagation loss, device immaturity, signal processing complexity, and testability. This paper aims to review the current progress on the development of the mmWave technology from seven areas of particular interest/myths with a particular focus on deployment feasibility. We also promote sensible discussions on the potential solutions. Finally, we ask the title question from a network operator's perspective.